Preparation method and application of 3D-CNS-coated Mo2Ti2C3TxMXene composite derivative

The 3D-CNS@Mo2Ti2C3TxMXene composite derivative prepared by acid treatment pre-etching and constant voltage plating processes solves the problems of slow kinetics of traditional battery materials and insufficient energy storage of supercapacitors, and achieves high power and high energy density lithium storage performance.

CN119637855AActive Publication Date: 2025-03-18ZHENGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411673490.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-18
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing battery materials have slow kinetics during diffusion-controlled redox processes, resulting in low power density; while supercapacitors have shortcomings in energy storage, making it difficult to take into account both high power and high energy density.

Method used

Acid treatment pre-etching combined with constant voltage plating and sintering technology were used to prepare a negative electrode material of three-dimensional porous carbon nanotubes and Mo2Ti2C3TxMXenes matrix composite.

Benefits of technology

It realizes lithium storage performance with high power and energy, and improves the specific capacity of lithium storage under large current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637855A_ABST
    Figure CN119637855A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a 3D-CNS-coated Mo2Ti2C3Tx MXene composite derivative, and belongs to the field of secondary battery negative electrode materials. The preparation method comprises the following steps: taking ferrocene as a precursor of a catalyst, taking 1, 2-dichlorobenzene as a carbon source, and preparing 3D-CNS through chemical vapor deposition; hydrofluoric acid is adopted for pre-etching, and multiple layers of Mo < 2 > Ti < 2 > C < 3 > T < x > M < xenes > are prepared; the 3D-CNS is used as a flexible substrate, a multi-layer Mo2Ti2C3Tx MXene solution is used as an electroplating solution, a platinum sheet is used as a counter electrode, and electroplating is carried out under constant voltage; and then, carrying out freeze drying, and sintering under the protection of inert gas, so as to obtain the 3D-CNS-coated Mo2Ti2C3Tx MXene composite derivative. The prepared integrated self-supporting electrode has the lithium storage performance of high power type and energy type.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery negative electrode materials, in particular to a three-dimensional porous carbon nanotube and Mo 2 Ti 2 C 3 T x MXenes-based composite negative electrode materials and their preparation methods and applications. Background Art

[0002] At present, electric vehicles (EVs) are increasingly favored by society due to their green and sustainable advantages in many aspects, such as intelligent connectivity, high energy efficiency, environmental friendliness, and diverse energy sources. However, compared with fuel vehicles, the range of electric vehicles is still limited; compared with the refueling time of fuel vehicles, the charging time of electric vehicles is still longer; at the same time, the energy storage capacity of automotive batteries still gradually decreases with the increase of usage time, resulting in relatively high battery costs.

[0003] Traditional battery materials, due to their diffusion-controlled redox processes, have slow electrochemical kinetics, resulting in high energy density and relatively low power density; supercapacitors have very fast charging times (on the order of seconds) due to their surface or near-surface controlled ion adsorption charge storage mechanisms, but their energy storage capacity is relatively low. A large number of previous studies have confirmed that pseudocapacitive materials have a redox reaction charge storage mechanism similar to battery materials, but their rate performance is comparable to that of traditional electrochemical double-layer capacitors; therefore, these materials provide a way to develop electrodes that achieve both high power density and considerable energy density.

[0004] Two-dimensional transition metal carbons and / or nitrides - Mxenes (general formula: M n+1 X n T x ;n=1-4; M=Ti, Nb, Mo, V, Zr...; X=C, N; T x= -O, -OH, -F, -Cl......), was first reported by the research group of Professor Yury Gogotsi of Drexel University in 2011. Since then, it has quickly attracted extensive research attention due to its intrinsic physical and chemical properties suitable for energy storage electrodes, such as metal-like conductivity, rich and adjustable surface functional groups, and two-dimensional ion transport channels. At present, due to the van der Waals force between MXenes sheets, which makes the sheets easy to self-stack, and the MXene pseudocapacitive charge storage mechanism, the embedded ions and the surface functional groups of MXenes only induce a slight redox depth. At the same time, the intrinsic rigidity of the MX bonds inside MXene makes it difficult to deform to accommodate foreign ions. Therefore, the lithium storage capacity of MXenes in actual energy storage applications still cannot meet people's demand for high-power and high-energy density materials.

[0005] Compared with the mature and complete preparation methods of single-metal MXenes, the preparation process of bimetallic MXenes with more atomic layers and larger interlayer spacing, including etching and subsequent interlayer peeling, is still relatively complicated and time-consuming. In addition, compared with the currently reported single-metal MXenes-based electrode materials, the synthesized bimetallic MXenes electrode materials do not show significant competitive advantages in lithium storage performance, cycle stability and rate capability. However, the rich metal composition of bimetallic MXenes M positions makes them exhibit diverse structures and physicochemical properties, making them still ideal candidates for energy storage materials. The electrical properties and electrochemical behaviors of bimetallic MXenes nanosheets remain to be explored. Summary of the invention

[0006] The present invention uses 413 MAX phase-Mo 2 Ti 2 AlC 3 As an example, a method of preparing three-dimensional carbon nanotube sponge (3D-CNS)-Mo by using acid treatment pre-etching combined with constant voltage electroplating and sintering is demonstrated. 2 Ti 2 C 3 T x Composite derivative strategy of MXene. First, the pre-etched multilayer Mo 2 Ti 2 C 3 T x MXenes were electroplated on 3D-PCNS (three-dimensional porous carbon nanosheets) to obtain 3D-CNS and Mo 2 Ti 2 C 3 T xSecondly, the composite was dried using a freeze-drying device to obtain a composite derivative precursor with a certain degree of flexibility. Finally, under the protection of an inert gas, the obtained precursor electrode sheet was heat-treated and sintered to form an integrated self-supporting 3D-CNS@Mo 2 Ti 2 C 3 T x MXene composite derivative electrode. The prepared integrated self-supporting electrode delivers high-power and energy-type lithium storage performance.

[0007] To achieve the above object, the technical solution adopted by the present invention is: A 3D-CNS@Mo 2 Ti 2 C 3 T x The preparation method of the composite derivative of MXene comprises the following steps: (1) Preparation of 3D-CNS Ferrocene was used as a catalyst precursor and 1,2-dichlorobenzene was used as a carbon source, synthesized by chemical vapor deposition technique; (2) Multi-layer Mo 2 Ti 2 C 3 T x Preparation of MXenes Using hydrofluoric acid for pre-etching, multilayer Mo with different morphologies and yields was prepared by different process parameters. 2 Ti 2 C 3 T x Mxenes; (3) 3D-CNS@Mo 2 Ti 2 C 3 T x Preparation of composite derivatives of MXene Acid treatment: 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and then washed with deionized water until neutral; Plating solution: prepared multilayer Mo 2 Ti 2 C 3 T x MXenes solution was prepared into 0.5-2 M aqueous solution and probe sonicated in an ice bath for 30 min; Electroplating process: The concentrated nitric acid hydrothermal treatment 3D-CNS as a flexible substrate, multilayer Mo 2 Ti 2 C 3 T xThe MXenes solution was used as the electroplating solution, and the platinum sheet was used as the counter electrode. The electroplating time was 5 min-60 min at a constant voltage of 3 V-20 V. Heat treatment: 3D-CNS@Mo after electroplating 2 Ti 2 C 3 T x The precursor substrate of the composite derivative of MXene is freeze-dried and sintered at 400℃-600℃ for 1 h-3 h under inert gas protection.

[0008] Furthermore, the specific process parameters for preparing 3D-CNS in step (1) are as follows: Solution preparation: Dissolve ferrocene powder in 1,2-dichlorobenzene to a concentration of 0.03-0.08 g mL -1 of solution; Solution delivery: 0.1-0.2 mL·min -1 The solution of the previous step is continuously injected into the quartz tube in the resistance furnace through the injection pump at a rate of Reaction conditions: Set the furnace temperature to 700-1000°C; Gas delivery: A mixture of argon and hydrogen was used as the carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 ; Growth substrate: Place a 2-inch × 1-inch quartz sheet in the reaction area as the growth substrate for the carbon nanotube sponge; Collecting the product: After 2-5 h of growth time, the three-dimensional carbon nanotube sponge with a certain thickness is collected from the quartz substrate.

[0009] Further, the specific process of the pre-etching is: Bimetallic MAX phase precursor: Mo 2 Ti 2 AlC 3 The amount added is 0.5 g-3 g; Etchant: 49 wt% HF, added amount 15 mL-40 mL; Pre-etching time: 120 h-168 h to ensure sufficient pre-etching effect; Pre-etching temperature: 55℃-65℃ to optimize the etching reaction. By adjusting the amount of MAX phase and HF added and the etching time, multi-layer Mo with different properties can be prepared. 2 Ti 2 C 3 T x Different combinations of these variables will affect the morphology and yield of the final product.

[0010] A 3D-CNS@Mo prepared by the above preparation method 2 Ti 2 C 3 T x Composite derivatives of MXene are used as negative electrode materials in lithium-ion batteries.

[0011] Furthermore, the 3D-CNS@Mo 2 Ti 2 C 3 T x The composite derivatives of MXene are used as negative electrode materials in lithium-ion batteries with a lithium storage capacity of 726 mAh / g at a current density of 5 A / g.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses electroplating process combined with subsequent heat treatment to prepare 3D-CNS@Mo 2 Ti 2 C 3 T x Composite derivatives of MXene, prepared 3D-CNS@Mo 2 Ti 2 C 3 T x Composite derivatives of MXene, Mo 2 Ti 2 C 3 T x The electrochemically inactive MX bonds in MXenes are effectively activated, which effectively enriches the lithium storage sites of the derivative materials, while synergistically inheriting and exerting the excellent conductivity and good flexibility of 3D-CNS. It also further improves the lithium storage capacity of the derivative materials at high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The multilayer Mo prepared in Example 1 of the present invention 2 Ti 2 C 3 T x Scanning electron microscope image of MXenes; Figure 2 3D-CNS@Mo prepared in Example 1 of the present invention 2 Ti 2 C 3 T x Transmission electron microscopy images of MXene composite derivatives; Figure 3 3D-CNS and 3D-CNS@Mo prepared in Example 1 of the present invention 2 Ti2 C 3 T x XRD test results of MXene composite derivatives; Figure 4 3D-CNS@Mo prepared in Example 1 of the present invention 2 Ti 2 C 3 T x Composite derivatives of MXene, 3D-CNS and multilayer Mo 2 Ti 2 C 3 T x Comparison of cycle performance curves of MXenes negative electrode materials. DETAILED DESCRIPTION

[0014] The technical solution and effects of the present invention are further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto. Example 1

[0015] A 3D-CNS@Mo 2 Ti 2 C 3 T x The preparation method of the composite derivative of MXene comprises the following steps: (1) Will Mo 2 Ti 2 AlC 3 Fabrication of multilayer Mo by HF pre-etching of MAX phase 2 Ti 2 C 3 T x MXenes; Preparation of multilayer Mo by liquid phase etching 2 Ti 2 C 3 T x MXenes, the specific method is as follows: In the preparation of Mo 2 Ti 2 C 3 T x In the MXenes precursor process, 49 wt% HF was used as an etchant. First, a polytetrafluoroethylene beaker with a hole was placed in a water bath. Next, 30 mL of HF was added to the polytetrafluoroethylene beaker using a pipette. Then, 2 g Mo 2 Ti 2 AlC 3MAX phase, and gradually added it to the hydrofluoric acid solution to ensure that the powder was evenly dispersed, and finally started the constant temperature water bath stirrer. The pre-etching process was carried out at 60 ° C for 144 h, and the stirring speed was set to 500 r min -1 After pre-etching, wash with deionized water and high-speed centrifuge until the pH value of the supernatant reaches neutral. Figure 1 Shows the multilayer Mo after pre-etching 2 Ti 2 C 3 T x Scanning electron microscope (SEM) image of MXenes.

[0016] (2) 3D-CNS was prepared by CVD method. The specific method is as follows: 3D-CNS was synthesized by CVD technology using ferrocene as a catalyst and 1,2-dichlorobenzene as a carbon source. First, ferrocene powder was dissolved in 1,2-dichlorobenzene to prepare 0.06 g mL -1 Then, the syringe pump was used to inject the solution at a rate of 0.13 mL min -1 The solution was continuously delivered to the quartz tube in the resistance furnace at a rate of 860°C. Ar and H 2 The mixed gas was used as carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 . A quartz sheet was placed in the reaction area as the growth substrate for 3D-CNS. After 2 h of growth, 3D-CNS with a certain thickness was collected from the quartz substrate. 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and washed with deionized water until neutral to obtain 3D-CNS@Mo 2 Ti 2 C 3 T x Free-standing substrates of composite derivatives of MXene.

[0017] (3) Preparation of 3D-CNS@Mo by electroplating and heat treatment process 2 Ti 2 C 3 T x The composite derivatives of MXene are as follows: The multilayer Mo 2 Ti 2 C 3 T xThe MXene solution was prepared into a 1 M plating solution, and the ice bath probe was ultrasonicated for 30 min. Then the 3D-CNS treated with concentrated nitric acid was used as an electrode, and the metal platinum sheet was used as a counter electrode. The electroplating was carried out at a constant voltage of 5 V for 30 min. 2 Ti 2 C 3 T x The precursor substrate of the composite derivative of MXene was freeze-dried and sintered at 500 °C for 2 h under inert gas protection.

[0018] The 3D-CNS@Mo prepared in this example 2 Ti 2 C 3 T x Transmission electron microscopy images of MXene composite derivatives are shown below: Figure 2 As shown in Figure 2, MXene nanosheets are uniformly loaded on the 3D-CNS matrix.

[0019] In this embodiment, CVD method is used to prepare 3D-CNS and electroplating method and heat treatment process are used to prepare 3D-CNS@Mo 2 Ti 2 C 3 T x XRD patterns of MXene composite derivatives Figure 3 Among them, the characteristic peaks around 25° and 45° correspond to the highly ordered graphite carbon in the 3D-CNS matrix.

[0020] The multilayer Mo prepared in step (1) of Example 1 2 Ti 2 C 3 T x Mxenes, 3D-CNS prepared in step (2), and 3D-CNS@Mo prepared in step (3) 2 Ti 2 C 3 T x The composite derivatives of MXene are used as negative electrode materials, Mo 2 Ti 2 C 3 T x Mxenes brushed battery, 3D-CNS and 3D-CNS@Mo 2 Ti 2 C 3 T x The composite derivatives of MXene were directly cut into pieces and assembled into batteries to test the electrochemical properties of the materials. Among them, the metal lithium sheet was used as the counter electrode, Celgard 2500 was used as the separator, and the electrolyte was 1 M LiPF 6(EC∶DMC=1∶1 vol%). Cycle performance curve comparison diagram is shown in Figure 4 As shown in Figure 2, at a current density of 5 A / g, after 100 cycles, 3D-CNS@Mo 2 Ti 2 C 3 T x MXene composite derivatives, 3D-CNS, multilayer Mo 2 Ti 2 C 3 T x The lithium storage capacity of MXenes is 726 mAh / g, 176 mAh / g, and 106 mAh / g, respectively. Example 2

[0021] A 3D-CNS@Mo 2 Ti 2 C 3 T x The preparation method of the composite derivative of MXene comprises the following steps: (1) Will Mo 2 Ti 2 AlC 3 Fabrication of multilayer Mo by HF pre-etching of MAX phase 2 Ti 2 C 3 T x MXenes; Preparation of multilayer Mo by liquid phase etching 2 Ti 2 C 3 T x MXenes, the specific method is as follows: In the preparation of Mo 2 Ti 2 C 3 T x In the MXenes precursor process, 49wt% HF was used as an etchant. First, a polytetrafluoroethylene beaker with a hole was placed in a water bath. Next, 40 mL of HF was added to the polytetrafluoroethylene beaker using a pipette. Then, 2g Mo 2 Ti 2 AlC 3 The MAX phase was gradually added to the hydrofluoric acid solution to ensure that the powder was evenly dispersed, and finally the constant temperature water bath agitator was started. The pre-etching process was carried out at 55 °C for 168 h, and the stirring speed was set to 500 r·min -1 After pre-etching, wash with deionized water and high-speed centrifuge until the pH value of the supernatant reaches neutral.

[0022] (2) 3D-CNS was prepared by CVD method. The specific method is as follows: 3D-CNS was synthesized by CVD technology using ferrocene as a catalyst and 1,2-dichlorobenzene as a carbon source. First, ferrocene powder was dissolved in 1,2-dichlorobenzene to prepare 0.04 g mL -1 Then, the syringe pump was used to inject the solution at a rate of 0.13 mL min -1 The solution was continuously delivered to the quartz tube in the resistance furnace at a rate of 1.5 %. At a reaction temperature of 960 °C, Ar and H 2 The mixed gas was used as carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 . A quartz sheet was placed in the reaction area as the growth substrate for 3D-CNS. After 4 h of growth, 3D-CNS with a certain thickness was collected from the quartz substrate. 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and washed with deionized water until neutral to obtain 3D-CNS@Mo 2 Ti 2 C 3 T x Free-standing substrates of composite derivatives of MXene.

[0023] (3) Preparation of 3D-CNS@Mo by electroplating and heat treatment process 2 Ti 2 C 3 T x The composite derivatives of MXene are as follows: The multilayer Mo 2 Ti 2 C 3 T x The MXene solution was prepared into a 1 M electroplating solution, and the ice bath probe was ultrasonicated for 30 min. Then the 3D-CNS treated with concentrated nitric acid was used as an electrode, and the metal platinum sheet was used as a counter electrode. The electroplating was carried out at a constant voltage of 5 V for 60 min. 2 Ti 2 C 3 T x The precursor substrate of the composite derivative of MXene was freeze-dried and sintered at 600 °C for 1 h under inert gas protection. Example 3

[0024] A 3D-CNS@Mo 2 Ti 2 C 3 T x The preparation method of the composite derivative of MXene comprises the following steps: (1) Will Mo 2 Ti 2 AlC 3 Fabrication of multilayer Mo by HF pre-etching of MAX phase 2 Ti 2 C 3 T x MXenes; Preparation of multilayer Mo by liquid phase etching 2 Ti 2 C 3 T x MXenes, the specific method is as follows: In the preparation of Mo 2 Ti 2 C 3 T x In the MXenes precursor process, 49 wt% HF was used as an etchant. First, a polytetrafluoroethylene beaker with a hole was placed in a water bath. Next, 30 mL of HF was added to the polytetrafluoroethylene beaker using a pipette. Then, 2 g Mo 2 Ti 2 AlC 3 MAX phase, and gradually added it to the hydrofluoric acid solution to ensure that the powder was evenly dispersed, and finally started the constant temperature water bath stirrer. The pre-etching process was carried out at 65 ° C for 120 h, and the stirring speed was set to 500 r min -1 After pre-etching, wash with deionized water and high-speed centrifuge until the pH value of the supernatant reaches neutral.

[0025] (2) 3D-CNS was prepared by CVD method. The specific method is as follows: 3D-CNS was synthesized by CVD technology using ferrocene as a catalyst and 1,2-dichlorobenzene as a carbon source. First, ferrocene powder was dissolved in 1,2-dichlorobenzene to prepare 0.05 g mL -1 Then, the syringe pump was used to inject the solution at a rate of 0.13 mL min -1 The solution was continuously delivered to the quartz tube in the resistance furnace at a rate of 1.5 %. At a reaction temperature of 760 °C, Ar and H 2 The mixed gas was used as carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 . A quartz sheet was placed in the reaction area as the growth substrate for 3D-CNS. After 2 h of growth, 3D-CNS with a certain thickness was collected from the quartz substrate. 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and washed with deionized water until neutral to obtain 3D-CNS@Mo2 Ti 2 C 3 T x Free-standing substrates of composite derivatives of MXene.

[0026] (3) Preparation of 3D-CNS@Mo by electroplating and heat treatment process 2 Ti 2 C 3 T x The composite derivatives of MXene are as follows: The multilayer Mo 2 Ti 2 C 3 T x The MXene solution was prepared into a 0.5 M plating solution, and the ice bath probe was ultrasonicated for 30 min. Then the 3D-CNS treated with concentrated nitric acid was used as an electrode, and the metal platinum sheet was used as a counter electrode. The electroplating was carried out at a constant voltage of 10 V for 10 min. 2 Ti 2 C 3 T x The precursor substrate of the composite derivative of MXene was freeze-dried and sintered at 400 °C for 3 h under inert gas protection. Example 4

[0027] A 3D-CNS@Mo 2 Ti 2 C 3 T x The preparation method of the composite derivative of MXene comprises the following steps: (1) Will Mo 2 Ti 2 AlC 3 Fabrication of multilayer Mo by HF pre-etching of MAX phase 2 Ti 2 C 3 T x MXenes; Preparation of multilayer Mo by liquid phase etching 2 Ti 2 C 3 T x MXenes, the specific method is as follows: In the preparation of Mo 2 Ti 2 C 3 T xIn the MXenes precursor process, 49 wt% HF was used as an etchant. First, a polytetrafluoroethylene beaker with a hole was placed in a water bath. Next, 30 mL of HF was added to the polytetrafluoroethylene beaker using a pipette. Then, 2 g Mo 2 Ti 2 AlC 3 MAX phase, and gradually added it to the hydrofluoric acid solution to ensure that the powder was evenly dispersed, and finally started the constant temperature water bath stirrer. The pre-etching process was carried out at 60 ° C for 144 h, and the stirring speed was set to 500 r min -1 After pre-etching, wash with deionized water and high-speed centrifuge until the pH value of the supernatant reaches neutral.

[0028] (2) 3D-CNS was prepared by CVD method. The specific method is as follows: 3D-CNS was synthesized by CVD technology using ferrocene as a catalyst and 1,2-dichlorobenzene as a carbon source. First, ferrocene powder was dissolved in 1,2-dichlorobenzene to prepare 0.03 g mL -1 Then, the syringe pump was used to inject the solution at a rate of 0.13 mL min -1 The solution was continuously delivered to the quartz tube in the resistance furnace at a rate of 800°C. Ar and H 2 The mixed gas was used as carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 . A quartz sheet was placed in the reaction area as the growth substrate for 3D-CNS. After 5 h of growth, 3D-CNS with a certain thickness was collected from the quartz substrate. 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and washed with deionized water until neutral to obtain 3D-CNS@Mo 2 Ti 2 C 3 T x Free-standing substrates of composite derivatives of MXene.

[0029] (3) Preparation of 3D-CNS@Mo by electroplating and heat treatment process 2 Ti 2 C 3 T x The composite derivatives of MXene are as follows: The multilayer Mo 2 Ti 2 C 3 T xThe MXene solution was prepared into a 1.5 M plating solution, and the ice bath probe was ultrasonicated for 30 min. Then the 3D-CNS treated with concentrated nitric acid was used as an electrode, and the metal platinum sheet was used as a counter electrode. The electroplating was carried out at a constant voltage of 15 V for 5 min. 2 Ti 2 C 3 T x The precursor substrate of the composite derivative of MXene was freeze-dried and sintered at 500 °C for 2 h under inert gas protection. Example 5

[0030] A 3D-CNS@Mo 2 Ti 2 C 3 T x The preparation method of the composite derivative of MXene comprises the following steps: (1) Will Mo 2 Ti 2 AlC 3 Fabrication of multilayer Mo by HF pre-etching of MAX phase 2 Ti 2 C 3 T x MXenes; Preparation of multilayer Mo by liquid phase etching 2 Ti 2 C 3 T x MXenes, the specific method is as follows: In the preparation of Mo 2 Ti 2 C 3 T x In the MXenes precursor process, 49 wt% HF was used as an etchant. First, a polytetrafluoroethylene beaker with a hole was placed in a water bath. Next, 30 mL of HF was added to the polytetrafluoroethylene beaker using a pipette. Then, 2 g Mo 2 Ti 2 AlC 3 MAX phase, and gradually added it to the hydrofluoric acid solution to ensure that the powder was evenly dispersed, and finally started the constant temperature water bath stirrer. The pre-etching process was carried out at 60 ° C for 144 h, and the stirring speed was set to 500 r min -1 After pre-etching, wash with deionized water and high-speed centrifuge until the pH value of the supernatant reaches neutral.

[0031] (2) 3D-CNS was prepared by CVD method. The specific method is as follows: 3D-CNS was synthesized by CVD technology using ferrocene as a catalyst and 1,2-dichlorobenzene as a carbon source. First, ferrocene powder was dissolved in 1,2-dichlorobenzene to prepare 0.08 g mL -1 Then, the syringe pump was used to inject the solution at a rate of 0.13 mL min -1 The solution was continuously delivered to the quartz tube in the resistance furnace at a rate of 1.5 %. At a reaction temperature of 900 °C, Ar and H 2 The mixed gas was used as carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 . A quartz sheet was placed in the reaction area as the growth substrate for 3D-CNS. After 5 h of growth, 3D-CNS with a certain thickness was collected from the quartz substrate. 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and washed with deionized water until neutral to obtain 3D-CNS@Mo 2 Ti 2 C 3 T x Free-standing substrates of composite derivatives of MXene.

[0032] (3) Preparation of 3D-CNS@Mo by electroplating and heat treatment process 2 Ti 2 C 3 T x The composite derivatives of MXene are as follows: The prepared multilayer Mo 2 Ti 2 C 3 T x The MXene solution was prepared into a 1 M plating solution, and the ice bath probe was ultrasonicated for 30 min. Then the 3D-CNS treated with concentrated nitric acid was used as an electrode, and the metal platinum sheet was used as a counter electrode. The electroplating was carried out at a constant voltage of 20 V for 5 min. 2 Ti 2 C 3 T x The precursor substrate of the composite derivative of MXene was freeze-dried and sintered at 500 °C for 2 h under inert gas protection. Comparative Example 1

[0033] This comparative example is the same as Example 1, except that: in step (1), a multilayer Mo is prepared 2 Ti 2 C 3 T xThe MXenes aqueous solution was freeze-dried without step (3), and then the battery was installed to test the electrical performance. The multilayer Mo prepared in step (1) 2 Ti 2 C 3 T x MXenes negative electrode materials have low specific lithium storage capacity, such as Figure 4 shown. Comparative Example 2

[0034] This comparative example is the same as Example 1, except that: in step (2), the 3D-CNS prepared was not subjected to step (3), and was directly cut into pieces and assembled into batteries for testing electrical performance. The 3D-CNS negative electrode material prepared in step (2) has a low specific lithium storage capacity, such as Figure 4 shown.

[0035] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A 3D-CNS@Mo2Ti2C3T x The method for preparing a composite derivative of MXene is characterized in that: The preparation method comprises the following steps: (1) Preparation of 3D-CNS Ferrocene was used as a catalyst precursor and 1,2-dichlorobenzene was used as a carbon source, synthesized by chemical vapor deposition technique; (2) Multilayer Mo2Ti2C3T x Preparation of MXenes Hydrofluoric acid was used for pre-etching, and multilayer Mo2Ti2C3T with different morphologies and yields were prepared by different process parameters. x Mxenes; (3) 3D-CNS@Mo2Ti2C3T x Preparation of composite derivatives of MXene Acid treatment: 3D-CNS was hydrothermally treated with concentrated nitric acid at 120 °C for 12 h, and then washed with deionized water until neutral; Plating solution: prepared multilayer Mo2Ti2C3T x The MXenes solution was prepared into a 0.5-2 M plating solution and the probe was sonicated in an ice bath for 30 min; Electroplating process: The concentrated nitric acid hydrothermal treatment 3D-CNS as a flexible substrate, multilayer Mo2Ti2C3T x The MXene solution was used as the electroplating solution, and the platinum sheet was used as the counter electrode. The electroplating time was 5 min-60 min at a constant voltage of 3 V-20 V. Heat treatment: 3D-CNS@Mo2Ti2C3T after electroplating x The precursor substrate of the composite derivative of MXene is freeze-dried and sintered at 400℃-600℃ for 1 h-3 h under inert gas protection.

2. The 3D-CNS@Mo2Ti2C3T according to claim 1 x The method for preparing a composite derivative of MXene is characterized in that: The specific process parameters for preparing 3D-CNS in step (1) are as follows: Solution preparation: Dissolve ferrocene powder in 1,2-dichlorobenzene to a concentration of 0.03-0.08 g mL -1 of solution; Solution delivery: 0.1-0.2 mL·min -1 The solution of the previous step is continuously injected into the quartz tube in the resistance furnace through the injection pump at a rate of Reaction conditions: Set the furnace temperature to 700-1000°C; Gas delivery: A mixture of argon and hydrogen was used as the carrier gas, and the flow rate was set to 2000 mL min -1 and 300 mL·min -1 ; Growth substrate: Place a 2-inch × 1-inch quartz sheet in the reaction area as the growth substrate for the carbon nanotube sponge; Collecting the product: After 2-5 h of growth time, the three-dimensional carbon nanotube sponge with a certain thickness is collected from the quartz substrate.

3. The 3D-CNS@Mo2Ti2C3T according to claim 1 x The method for preparing a composite derivative of MXene is characterized in that: The specific process of the pre-etching is: Bimetallic MAX phase precursor: Mo2Ti2AlC3 addition amount is 0.5 g-3 g; Etchant: 49 wt% HF, added amount 15 mL-40 mL; Pre-etching time: 120 h-168 h to ensure sufficient pre-etching effect; Pre-etching temperature: 55℃-65℃ to optimize the etching reaction. By adjusting the amount of MAX phase and HF added and the etching time, multilayer Mo2Ti2C3T with different properties can be prepared. x Different combinations of these variables will affect the morphology and yield of the final product.

4. A 3D-CNS@Mo2Ti2C3T x A composite derivative of MXene, characterized in that The compound is prepared by the preparation method described in any one of claims 1 to 3.

5. The 3D-CNS@Mo2Ti2C3T according to claim 4 x A composite derivative of MXene, characterized in that The 3D-CNS@Mo2Ti2C3T x Composite derivatives of MXene are used as negative electrode materials in lithium-ion batteries.

6. The 3D-CNS@Mo2Ti2C3T according to claim 5 x A composite derivative of MXene, characterized in that The 3D-CNS@Mo2Ti2C3T x The composite derivatives of MXene are used as negative electrode materials in lithium-ion batteries with a lithium storage capacity of 726 mAh / g at a current density of 5 A / g.

Citation Information

Patent Citations

  • Preparation method of microbial fuel cell anode loaded with MXene on carbonized loofah sponge

    CN110350210A

  • Preparation method of low-temperature MXenes-based in-situ growth CNTs composite material

    CN117486204A

  • Bimetal Mo2Ti2C3Tx-based hybrid negative electrode material and preparation method and application thereof

    CN118016883A